Larvicidal activity of acacia nilotica extracts and isolation of D-pinitol - a bioactive carbohydrate - Chaubal, Rohini; Pawar, P. V.; Hebbalkar, G. D.; Tungikar, V. B.; Puranik, Vedavati G.; Deshpande, V. H.; Deshpande, N. R. (Chemistry & Biodiversity, 2005)
A low-molecular-weight, sugar-like compound other than glucose, fructose, sucrose, or myo-inositol showing lipophilic nature was isolated from the EtOH extract of Acacia nilotica. The structure of the compound was determined by spectral methods. This alicyclic polyalcohol was found to be D-pinitol (- 3-O-methyl-D-chiro-inositol; 1). The configuration of the compound was confirmed by single-crystal X-ray analysis. The compound I is known from Soybean, Australian mangroves, Fagonia indica, A rachis hypogaea, etc., but we have isolated this compound for the first time from the aerial parts of A. nilotica. Very few references have been cited for compound I for its entomological activity, and there are no reports on mosquitoes. Therefore, the crude extracts of A. nilotica were tested for its biological activity against mosquito larvae. Acetone extract at 500-ppm concentration showed chronic toxicity against Aedes aegypti and Culex quinquefasciatus IVth instar mosquito larvae. Such a biological activity has been observed for the first time for this plant. This study could be a stepping stone to a solution for destroying larval species as well as consumption of such a widely grown, problem weed, A. nilotica. This larvicidal agent, since it is derived from plant, is eco-friendly, cost effective, non-hazardous to nontarget organisms and would be safe unlike commercially available insecticides.